Strategi Peningkatkan Repurchase Intention melalui Customer Experience dan Perceived Value dengan Brand Reputation sebagai Variabel Mediasi (Studi pada Konsumen CV. Cynthia Box Kudus) - Naufal Nur Ikhsan; Mulyana Mulyana (ARZUSIN, 2026)
Increasingly intense competition in the carton packaging industry requires companies not only to rely on product quality but also to pay attention to customer experience and perceived value in order to increase repurchase intention. Sales fluctuations at CV. Cynthia Box Kudus indicate instability in customers’ repurchase intention. This study aimed to analyze the effect of customer experience and perceived value on repurchase intention, with brand reputation as a mediating variable. This study used a quantitative approach with a survey method, involving 100 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results showed that customer experience had a positive and significant effect on brand reputation but did not have a significant effect on repurchase intention. Perceived value had a positive and significant effect on brand reputation and repurchase intention, while brand reputation had a positive and significant effect on repurchase intention. In addition, brand reputation was unable to mediate the relationship between customer experience and repurchase intention, but was able to mediate the relationship between perceived value and repurchase intention. These findings confirm that perceived value and brand reputation are dominant factors in increasing repurchase intention. The implications of this study indicate the importance of companies improving customers’ perceived value and maintaining brand reputation to strengthen customer loyalty in the long term.